Association between lactate/albumin ratio and 28-day mortality in ICU critical patients with coronary heart disease: a retrospective analysis of the MIMIC-IV database - Liu, Ying (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe serum lactate/albumin ratio (LAR) is commonly employed for monitoring and evaluating the prognosis of critically ill patients. Both elevated lactate levels and decreased albumin levels may reflect the body's stress response and inflammatory reaction. Coronary heart disease (CHD), with common complications including myocardial infarction, arrhythmia, heart failure, is one of the leading causes of global death. Therefore, it is crucial to explore biomarkers that can predict the prognosis and mortality of CHD patients.MethodsThis is a retrospective study in which the data is from the MIMIC-IV database. Our study assessed the association between LAR value and mortality within 28 days of admission in a total of 1,902 CHD patients from the Beth Israel Deaconess Medical Center.ResultsThe results demonstrated a significant increase in 28-day mortality among individuals with higher LAR values. Multivariate analysis by Cox proportional hazard model revealed an incremental rise in mortality across each quartile with the increase of LAR value. Furthermore, restricted cubic spline (RCS) Cox regression analysis further revealed that higher LAR values were associated with increased 28-day mortality in the CHD patients. And subgroup analysis confirmed that the LAR level could serve as an independent predictor of 28-day mortality with CHD patients.ConclusionsOur study demonstrated that the LAR value can be an important risk predictor of 28-day mortality in patients with CHD, and a higher LAR associate with increased mortality rate.